Peran Pemerintah Desa dalam Pengelolaan Dana Desa di Desa Bah Sidua Dua Kabupaten Serdang Bedagai - Saragih, Triana; Deliana, Marlina; Adam, Adam (Universitas Medan Area, 2025)
According to Government Regulation Number 60 of 2014, Village Funds sourced from the State Budget are allocated through the APBD to finance government, development, and community development. However, its implementation in Bah Sidua Dua Village has not fully run optimally. This study aims to analyze the role of village governments in the management of Village Funds and identify their inhibiting factors. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The analysis is based on P. Siagian's theory, which includes four indicators: stabilizer, innovator, pioneer, and modernisator. The results of the study show that the village government's efforts in managing the Village Fund are still not optimal. The people of Bah Sidua Dua Village feel that the village government does not prioritize infrastructure development, especially roads, which is their main need. In addition, the results of the search revealed that the role of the village government in the management of the Village Fund has not been carried out effectively. The main obstacle faced is budget limitations, so that the village government cannot fully realize the planned development program.